Combined effects of hypertension, hyperlipidemia, and diabetes mellitus on the presence and severity of carotid atherosclerosis in community-dwelling elders: A community-based study. Issue 2 (4th November 2022) - Lu, Shu-Xin; Wu, Tzu-Wei; Chou, Chao-Liang; Cheng, Chun-Fang; Wang, Li-Yu
Abstract : Background: Hypertension, hyperlipidemia, and diabetes mellitus (DM) are common cardiovascular disease (CVD) comorbidities and well-known major determinants of atherosclerosis. However, their combined effects and relative contributions have not been well explored. This study aimed to characterize the characteristics of carotid atherosclerosis and dissect the relative effects of these common CVD comorbidities on the presence and severity of carotid atherosclerosis in community-dwelling elderly individuals. Methods: We enrolled 817 elders from communities in northern Taiwan. We evaluated their cardiovascular risk profiles and scanned their extracranial carotid arteries using high-resolution ultrasonography systems. Results: The prevalence rates for hypertension, hyperlipidemia, and DM were 45.4%, 37.1%, and 16.8%, respectively. Sixty-two (7.6%) and 188 (23.0%) elderly had all three and two of these common CVD comorbidities, respectively. The prevalent rates of carotid plaque and moderate-to-severe atherosclerosis were 62.9% and 35.5%, respectively. The percentages of one or more common CVD comorbidities in elders with carotid plaque and moderate-to-severe atherosclerosis were 78.2% and 83.1%, respectively. Multivariate analyses showed that the number of common CVD comorbidities was the most predictive determinant. Multivariable-adjusted odds ratios (ORs) per comorbidity for the presence of carotid plaque and advanced carotid atherosclerosis were 1.52 (95% CI, 1.28-1.81) and 1.57 (95% CI, 1.28-1.93), respectively. Models containing hypertension and DM were the second most predictive. Combinatory analyses showed distinct relationship patterns between carotid atherosclerosis and hypertension, hyperlipidemia, and DM. Hypertension was significantly correlated with higher ORs for the presence of carotid plaque and advanced carotid atherosclerosis but not for hyperlipidemia. Conclusion: Carotid plaques are highly prevalent in community-dwelling elders. The number of common CVD comorbidities was the most predictive determinant of carotid plaques and advanced carotid atherosclerosis. Our results indicate that to reduce the impact of atherosclerotic diseases, blood pressure controls precede the control of blood lipids and glucose in the community-dwelling elders.